A study to assess the birth preparedness and complication readiness among antenatal women attending district hospital in Tumkur, Karnataka, India - P., Rajesh; R., Swetha; S., Rajanna M.; Iyengar, Krishna; H., Mahesh S.; Gowda, Cheluve (International Journal Of Community Medicine And Public Health, 2017)
Background: Globally, more than 40% of pregnant women may experience acute obstetric problems. Most of maternal deaths were due to delay in identifying the complication, deciding to seek care, identifying and reaching a health facility and receiving adequate and appropriate treatment at the health facility. Birth preparedness and complication readiness (BPACR) is an intervention that addresses these delays by encouraging pregnant women, their families, and communities to effectively plan for births and deal with emergencies, if they occur. Methods:A cross-sectional study was done among 371 antenatal women attending antenatal clinic in a District hospital. After getting consent, all of them were interviewed with a structured questionnaire. Results: Out of 371 pregnant mothers, only 133 (35.85%) were well prepared for child birth. 28.03% of women didn’t know even a single danger sign and 24.26% mentioned at least one danger sign. Only 23% of the pregnant women were sensitized by the health worker regarding the danger signs. Among the socio-demographic characteristics collected in this study, parity, education status of mother and husband and women who had child birth within 2 years was significantly associated with well preparedness status of BPACR. Conclusions:BPACR - preparedness was observed among 35.85%of pregnant mother. Awareness regarding danger signs during pregnancy, child birth and postpartum period were very poor. Preparedness was observed to improve with mother’s and spouse education status, increase in parity and women had child birth within two years were better prepared.